Prevalence of professional burnout among practicing cardiologists in the constituent entities of the Russian Federation - G. A. Neplyueva; A. E. Soloveva; S. D. Krovopolenova; A. E. Solovev; V. V. Zaitsev; N. E. Zvartau; A. O. Konradi; S. V. Villevalde (Российский кардиологический журнал, 2023)
The burnout syndrome among healthcare professionals is a headline problem in the world, as it leads to poor health of medical workers, affects patient satisfaction with health care and the healthcare system as a whole. At the same time, existing preventive measures can improve the well-being of staff.Aim. To study the prevalence of professional burnout syndrome among practicing cardiologists in the Russian Federation (RF).Material and methods. This cross-sectional study was carried out using the method of online anonymous surveying. The inclusion criterion was the current practical activity in the RF. The study involved 452 cardiologists from 8 federal districts (women; n=377, 83,4%), 48,2% of which worked in a hospital. Occupational burnout was assessed using the Maslach Burnout Inventory (MBI) questionnaire in the Russian language adaptation for healthcare workers by N. E. Vodopyanova and E. S. Starchenkova. The score was calculated on three subscales (emotional exhaustion, depersonalization, personal accomplishment), the maximum score for the subscales was 54, 30 and 48, respectively. The personal accomplishment subscale is the opposite as follows: the higher the score, the less the symptom severity. Additionally, demographic parameters, working conditions, the desire to change job and field of activity were taken into account. Regression analysis was used to establish associations of burnout with factors.Results. The median score of the emotional exhaustion subscale was 29,5 (23,0; 35,0) points, depersonalization — 12,0 (8,0; 16,0) and personal accomplishment — 32,0 (28,0; 37,0). Men had higher depersonalization score than women as follows: 15,0 (10,0; 18,0) vs 11,0 (8,0; 15,0), p=0,001. High degrees of emotional exhaustion and depersonalization (burnout) were found in 235 (52%) cardiologists, while all three symptoms simultaneously — in 132 (29,2%) doctors. There were no symptoms of burnout in 84 (18,6%) cardiologists. A high degree of burnout was associated with a desire to change job (p<0,001).Conclusion. A high prevalence of professional burnout among practicing cardiologists in the RF was revealed, which, in turn, is associated with the desire to change job or occupation.